Efficiency of navigation strategies for active particles in rugged landscapes - Piro, Lorenzo; Golestanian, Ramin; Mahault, Benoît (Frontiers in Physics, 2022)
Optimal navigation in complex environments is a problem with multiple applications ranging from designing efficient search strategies to engineering microscopic cargo delivery. When motion happens in presence of strong external forces, route optimization is particularly important as active particles may encounter trapping regions that would substantially slow-down their progress. Here, considering a self-propelled agent moving at constant speed we study the efficiency of Zermelo's classical solution for navigation in a sinusoidal potential landscape. Investigating both cases of motion on the plane and on curved surfaces, we focus on the regime where the external force exceeds self-propulsion in finite regions. There we show that, despite the fact that most trajectories following the trivial policy of going straight get arrested, the Zermelo policy allows for a comprehensive exploration of the environment. However, our results also indicate an increased sensitivity of the Zermelo strategy to initial conditions, which limits its robustness and long-time efficiency in particular in presence of fluctuations. These results suggest an interesting trade-off between exploration efficiency and stability for the design of control strategies to be implemented in real systems.